2022
DOI: 10.3390/su14010519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Settlements on Diversity of Range Vegetation

Abstract: The rapidly increasing population of human beings in semi-arid areas is often considered as a major factor of land degradation. Only a few studies have examined the dynamics of human settlements on the composition, diversity, structure and palatability of range vegetation in Southern Punjab Pakistan. The current study aims to assess whether the distance from settlements had any effect on the range vegetation’s diversity and cover. In order to determine the impact of human settlements on the vegetation, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
3
5
0
Order By: Relevance
“…Thus depicting lower vegetation cover as the distance from the villages increased. Further, it is also in line with Jamil et al [21], which also depicts the vegetation cover decreasing as the distance from the human settlements is increased. Our results are in accordance with a spatio-temporal determination of vegetation canopy cover using remote sensing, in which the authors concluded anthropogenic drivers, mainly distance from rural settlements and livestock density, had a major role to play in governing the vegetation cover of grasslands [58,59].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus depicting lower vegetation cover as the distance from the villages increased. Further, it is also in line with Jamil et al [21], which also depicts the vegetation cover decreasing as the distance from the human settlements is increased. Our results are in accordance with a spatio-temporal determination of vegetation canopy cover using remote sensing, in which the authors concluded anthropogenic drivers, mainly distance from rural settlements and livestock density, had a major role to play in governing the vegetation cover of grasslands [58,59].…”
Section: Discussionsupporting
confidence: 88%
“…However, a recent study conducted in the arid rangelands of southern Pakistan depicted heavy grazing in areas far from pastoral settlements. This study found that regions further away from the settlements had lower plant density and sparse vegetation cover compared to nearer sites [21].…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…The quadrats near the forest edge had a comparatively higher number of cow dung. The results are consistent with another study (Jamil et al, 2022) which showed livestock grazing intensity being higher closer to human settlement than in locations far away from human settlement.…”
Section: Relationship Between Cow Dung Presence and Seedlings/saplingssupporting
confidence: 92%
“…Rangelands help in the preservation of biodiversity and some of the species of plants that are used for medical purposes. Rangeland policies and implementations with respect to conservation are necessary for sustainable management ( Coppock et al, 2022 ; Farid et al, 2022 ; Jamil et al, 2022 ; Machan et al, 2022 ). It will assist in the nutrition of camels for improvement in their productive and reproductive performances ( Kuria et al, 2021 ).…”
Section: Pathways Towards Sustainable Camel Production and Conservati...mentioning
confidence: 99%